2016
DOI: 10.1039/c6cc06929k
|View full text |Cite
|
Sign up to set email alerts
|

S(vi) Lewis acids: fluorosulfoxonium cations

Abstract: Avenues to S-based Lewis acids were developed via the oxidation of aryl-sulfoxides with XeF, giving difluorodiarylsulfoxides which react via fluoride abstraction to afford Lewis acidic fluorosulfoxonium cations; this acidity is derived from the S-F σ* orbital and has been probed both experimentally and computationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…[191] S VI sulfoxonium cations where prepared recently by fluorination of aS IV precursor and fluoridea bstraction in substantial amounts( > 500 mg, Figure 7c). [192] The Lewis acidityo nt he GB scale clearlye xceeded that of B(C 6 F 5 ) 3 .T he FIA was calculated (non-isodesmic) as 604 kJ mol À1 in the gas phase and even higher (635 kJ mol À1 )i n solution (COSMO-RS). The higherF IA in solution is unexpected and also contradicts with the factt hat the cation is prepared by fluoridea bstractionw ith the weak Lewis acid BF 3 -OEt 2 .…”
Section: Group 16mentioning
confidence: 95%
See 1 more Smart Citation
“…[191] S VI sulfoxonium cations where prepared recently by fluorination of aS IV precursor and fluoridea bstraction in substantial amounts( > 500 mg, Figure 7c). [192] The Lewis acidityo nt he GB scale clearlye xceeded that of B(C 6 F 5 ) 3 .T he FIA was calculated (non-isodesmic) as 604 kJ mol À1 in the gas phase and even higher (635 kJ mol À1 )i n solution (COSMO-RS). The higherF IA in solution is unexpected and also contradicts with the factt hat the cation is prepared by fluoridea bstractionw ith the weak Lewis acid BF 3 -OEt 2 .…”
Section: Group 16mentioning
confidence: 95%
“…Even the perfluorinated sulfonium ion (CF 3 ) 2 SF + is stable towards AsF 6 − . S VI sulfoxonium cations where prepared recently by fluorination of a S IV precursor and fluoride abstraction in substantial amounts (>500 mg, Figure c) . The Lewis acidity on the GB scale clearly exceeded that of B(C 6 F 5 ) 3 .…”
Section: Overview Of Lewis Superacidsmentioning
confidence: 99%
“…[7] Other researchers have similarly broadened FLP chemistry to include C-, Si-and Sn-based Lewis acid species, [8] and we have also explored the potential of S-based Lewis acids. [9] Recently,weand others have turned our attention to the potential of nitrogen-based Lewis acids.Although N-containing compounds are usually considered basic due to the typical presence of alone pair of electrons,afew classes of nitrogen compounds are known to be N-centered electrophiles (Figure 1). [10] In what is best described as seminal work, Gandelman and co-workers [11] described several examples of the incorporation of triazolium cations into multidentate ligands where the nitreniums serve as donors,coordinating to transition metal centers.T his group has also demonstrated that such nitrenium cations behave as Lewis acids,f orming donor-acceptor adducts with ar ange of phosphines.…”
mentioning
confidence: 99%
“…While such species could be used as the Lewis acid component for FLP hydrogenation catalysis, they also proved useful for a broad range of reactions, including hydrodefluorination, dehydrocoupling, pseudo‐transfer hydrogenation, hydrosilylation, functionalization of CF and CF 3 fragments, and hydroarylation . Other researchers have similarly broadened FLP chemistry to include C‐, Si‐ and Sn‐based Lewis acid species, and we have also explored the potential of S‐based Lewis acids …”
Section: Figurementioning
confidence: 99%